Assay of mycobacterium tuberculosis in biopsy specimens taken from hepatic granuloma patients using polymerase chain reaction method - İlyas TUNCER and O. Kaya KÖKSALAN and Kadir DEMİR and Dinç DİNÇER and Salih TÜRKOĞLU and Sabahattin KAYMAKOĞLU and Uğur ÇEVİKBAŞ and; m BADUR and; la ÖKTEN and; az ÇAKALOĞLU (Turkish Journal of Gastroenterology, 2019)
-